STRATEGY TO IMPROVE PORT EMPLOYEE PERFORMANCE: ANALYSIS OF COMPETENCY, MOTIVATION, AND WORK DISCIPLINE AT UPP CLASS I TOBELO - Alnursa, Plening Gil; Marwan; Warlina, Lina (Branding: Jurnal Manajemen dan Bisnis, 2025)
This study aims to analyze the influence of competence, motivation, and work discipline on employee performance at the Class I Port Administration Office (UPP) in Tobelo. The research is based on operational issues linked to inadequate discipline, suboptimal training and competency development, and low work motivation among staff. A quantitative approach with an associative design was employed. The study involved all 55 employees as the total sample. Data were collected using a closed-ended Likert-scale questionnaire that had passed validity and reliability tests. Multiple linear regression analysis was conducted using SPSS version 25.0. The findings indicate that competence, motivation, and work discipline collectively have a significant impact on employee performance, with a coefficient of determination (R²) of 0.911. This suggests that 91.1% of the variation in performance is explained by the three variables. Partially, competence shows the strongest influence (β = 0.751), followed by motivation (β = 0.604). Interestingly, work discipline exerts a significant negative effect on performance (β = -0.314). These results highlight the importance of enhancing employee competence and motivation as key strategies for improving organizational performance. While discipline remains relevant, it should be implemented through consistent and measurable policies. The study recommends that human resource management in port offices prioritize career-based motivation strategies and continuous competence development to ensure sustained performance improvement.